Kepentingan Korea Selatan Dalam Kegiatan Perdagangan di Wilayah Asean Melalui Asean-Korean Free Trade Area (AKFTA) - Putra, Aldy Sugandi; Prinanda, Devita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
Participation in free trade has various impacts on member countries. This study aims to determine South Korea's Interests in Trade Activities in the Asean Region Through the Asean-Korean Free Trade Area (AKFTA). The method that the researcher uses is a qualitative method which aims to explain South Korea's interests in trade in the Southeast Asian region. The results of the study show that there is an increase that proves South Korea's interests in the ASEAN Region through AKFTA where to analyze South Korea's Interests in Trade Activities in the Asean Region Through the Asean-Korean Free Trade Area (AKFTA) researchers use the concept of national interest and the concept of strategic partners to explain what are the interests South Korea in trading activities in the Asean region through the Asean-Korean Free Trade Area (AKFTA) which in conclusion on the import side shows almost the same effect on the five product classifications, while on the export side the effect varies for each product classification.